2015
DOI: 10.3892/or.2015.4523
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed genes associated with hormones in terminal ductal lobular units identified by global transcriptome analysis: An insight into the anatomic origin of breast cancer

Abstract: Although human breast ducts and terminal ductal lobular units (TDLUs) share the same cell types, ample evidence shows that TDLUs are the predominant site for the origin of breast cancer. Yet, there is still limited information concerning the molecular mechanisms. Analysis of transcriptomic profiles in TDLUs may provide insight into early breast tumorigenesis. We compared genome-wide expression profiles of 8 matched sets of breast main duct and TDLU samples, using significance analysis of microarray (SAM) softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The TDLU is considered to be the predominant site of the origin of breast cancer. 12 The vast majority of breast cancers are carcinomas that arise in the epithelium and include in-situ and invasive ductal and invasive lobular carcinoma. Gene expression studies have indicated that hormone-related pathways are highly enriched in the TDLU, including various hormone-related genes that are associated with breast carcinogenesis.…”
Section: Immune Cells In the Normal Breastmentioning
confidence: 99%
See 2 more Smart Citations
“…The TDLU is considered to be the predominant site of the origin of breast cancer. 12 The vast majority of breast cancers are carcinomas that arise in the epithelium and include in-situ and invasive ductal and invasive lobular carcinoma. Gene expression studies have indicated that hormone-related pathways are highly enriched in the TDLU, including various hormone-related genes that are associated with breast carcinogenesis.…”
Section: Immune Cells In the Normal Breastmentioning
confidence: 99%
“…It has been proposed that the imbalanced hormone-reactions may result in the early onset of neoplastic transformation that occurs mostly in breast TDLUs. 12 The breast ducts are surrounded by stroma that consists of extracellular matrix (ECM), fibroblasts, adipocytes, immune cells, microbiome, and blood vessels. The breast ducts and stroma together comprise the breast microenvironment.…”
Section: Immune Cells In the Normal Breastmentioning
confidence: 99%
See 1 more Smart Citation
“…These three pathways are intimately connected in a feedback loop: EMT and up-regulation of the inflammatory response leads to secretion of inflammatory mediators including cytokines, chemokines, and matrix MMPs that create a pro-tumor microenvironment that enhances angiogenesis, induces EMT, and maintains inflammation through paracrine and autocrine effects (Figure 4B) (24). For BRCA, there was AFR up-regulation of 12 genes involved in response to estrogen and several genes involved in KRAS activation including HSD11B2, which is implicated in hormone metabolism and response and over-expressed in both breast cancer cell lines and breast tumors (Supplementary Table S6) (25). Estrogen has also been linked to breast cancer for its potential role as a mitogen stimulating cell division of breast tissue or as a carcinogen (26).…”
Section: Gene Set Enrichment Analysismentioning
confidence: 99%
“…1 ). TDLU, as implied by its name, consists of ductal branching networks and lobular structures containing milk-secreting acini [ 4 , 16 ].
Fig.
…”
Section: Anatomical and Histogenesis Portrayal Of The Myoepithelial C...mentioning
confidence: 99%